2016
DOI: 10.1557/adv.2016.230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Size on Mechanical Properties of Dual Phase Steels Composed of Ferrite and Martensite

Abstract: It is well-known that dual phase (DP) steels composed of ferrite and martensite have good ductility and plasticity as well as high strength. Due to their excellent mechanical properties, DP steels are widely used in the industrial field. The mechanical properties of DP steels strongly depend on several factors such as fraction, distribution and grain size of each phase. In this study, the grain size effect on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Generally, strength is mainly affected by grain size and martensite volume fraction for certain chemical composition in DP steel. 3,4) Therefore, it can be concluded that the bendability of DP steel is determined by the combined structural parameters, such as grain size, volume fraction as well as spatial distribution of martensite.…”
Section: Influencing Factors Of Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, strength is mainly affected by grain size and martensite volume fraction for certain chemical composition in DP steel. 3,4) Therefore, it can be concluded that the bendability of DP steel is determined by the combined structural parameters, such as grain size, volume fraction as well as spatial distribution of martensite.…”
Section: Influencing Factors Of Brmentioning
confidence: 99%
“…The effects of chemical composition, initial microstructure and processing parameters on the mechanical properties of DP steel have been addressed in many experimental and computational studies. [1][2][3][4] It is well known that the final microstructure of DP steels is determined by the initial microstructure and the processing parameters of the heating and intercritical dwelling stage. [5][6][7][8][9][10] Two interacting metallurgical phenomena, ferrite recrystallization and austenite formation take place during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…These microstructural factors are dependent on the chemical composition and the processing parameters in the intercritical annealing, and on the initial hot-rolled microstructure due to the microstructural heritage. [1][2][3][4][5][6][7][8] Among these, austenite formation has been extensively studied, including the influence of initial microstructures, [9][10][11][12] heating parameters, [2,6,13] the underlying mechanisms such as elements partitioning, and interface characteristics accompanied by the α/γ interface movement. [14][15][16][17] It is known that ferrite recrystallization also occurs during the intercritical annealing process, and these two metallurgical phenomena usually have an interaction effect [18,19] especially under a relatively high heating rate.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-phase (DP) steels consisting of soft ferrite phase and hard martensite phase are widely used steels due to their good mechanical balance between strength and ductility. Over several decades, many studies of DP steels have been achieving much better mechanical performance by changing microstructural factors such as phase distribution, grain size, phase strength (hardness) and phase fraction [1][2][3]. Recently, it has been found that the grain refinement for DP steels is a promising strategy to simultaneously improve strength and ductility IOP Publishing doi:10.1088/1757-899X/1249/1/012041 2 (especially post-uniform elongation) [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Over several decades, many studies of DP steels have been achieving much better mechanical performance by changing microstructural factors such as phase distribution, grain size, phase strength (hardness) and phase fraction [1][2][3]. Recently, it has been found that the grain refinement for DP steels is a promising strategy to simultaneously improve strength and ductility IOP Publishing doi:10.1088/1757-899X/1249/1/012041 2 (especially post-uniform elongation) [2,4]. However, the underlying reason for the enhancement of post-uniform elongation realized by grain refinement is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%